Pour une Approche pragmatique, écologique et politique de l’expertise - Marc Barbier; Lionel Cauchard; Pierre-Benoit Joly; Catherine Paradeise; Dominique Vinck (Revue d'anthropologie des connaissances)
The article offers a retrospective look at the study and sociological critique of expertise. The research has focused on its role in society, its legitimacy and its links to academic knowledge. As its legitimacy and credibility have been challenged by controversy and the issue of conflict of interest, the research was interested in its relationship to the functioning of politics and markets, as well as how to become an expert and the practice of expertise in the situation. Expertise is then studied as a social practice that combines know-how, understanding and assembling to reveal a problematic situation. The article gives an account of the constitution of two research orientations: one deals with the joint constitution of the statements and the infrastructures on which their creation is based; the other qualifies the situations in which ordinary knowledge is not sufficient to form a judgment or find a solution. It also deals with the transformations of the places of expertise (the emergence of think tanks in particular) and their practices (in particular the system of check and balance and advocacy), as well as policies (technical democratization) and forms of expertise management. The text aims to decentralise the way in which expertise has been seen to be owned by scientists. Instead, it proposes a reconstitution of relations and transfers of knowledge between the academic and "profane" (non-expert) worlds, between society and its respective authorities. The article advocates a pragmatic, ecological and political approach to expertise. Viewing expertise from a pragmatic approach, the heterogeneity of practices, the transformation of the knowledge-power relationship, in which the generation of knowledge is related to the inclusion of different groups of experts and the generation of new relationships, should be studied. The ecological approach describes the mechanisms of expertise and its governance and the construction of spaces for dialogue, resulting in the consolidation of expert knowledge in different problem situations. Finally, the text gives us a look at the modes of existence of the politics of expertise, its institutional and performative dimension, and its regulation. Therefore, the article suggests studying the devices of expertise and the perspectives that the actors deploy as experts.